2001
DOI: 10.1016/s0736-0266(00)00010-3
|View full text |Cite
|
Sign up to set email alerts
|

Age‐ and gender‐related changes in the cellularity of human bone marrow and the prevalence of osteoblastic progenitors

Abstract: Bone marrow harvested by aspiration contains connective tissue progenitor cells which can be induced to express a bone phenotype in vitro. The number of osteoblastic progenitors can be estimated by counting the colony-forming units which express alkaline phosphatase (CFU-APs). This study was undertaken to test the hypothesis that human aging is associated with a significant change in the number or prevalence of osteoblastic progenitors in the bone marrow. Four 2-ml bone marrow aspirates were harvested bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
293
2
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(320 citation statements)
references
References 21 publications
19
293
2
6
Order By: Relevance
“…Other reports demonstrated that osteogenic progenitor cells were maintained during aging [47][48][49]. The question of changes in the osteoprogenitor cell population with age is further complicated by the possibility of sex-dependent differences [50][51][52]. Age-related osteoponia may also depend from the skeletal site, depending to the variable trabecular-cortical bone ratio at different locations [53].…”
Section: Discussionmentioning
confidence: 99%
“…Other reports demonstrated that osteogenic progenitor cells were maintained during aging [47][48][49]. The question of changes in the osteoprogenitor cell population with age is further complicated by the possibility of sex-dependent differences [50][51][52]. Age-related osteoponia may also depend from the skeletal site, depending to the variable trabecular-cortical bone ratio at different locations [53].…”
Section: Discussionmentioning
confidence: 99%
“…In the bovine, Dowthwaite et al [88] have suggested that stem/progenitor cells on the articular surfaces achieve appositional cartilage growth; these cells expressed the α5β1 integrin, the classical fibronectin receptor and Notch 1, which appeared to identify the most clonogenic cells. Osteoblastic progenitors can be recognized in vitro as cells that make colonies that express alkaline phosphatase (CFU-APs), and in humans there are on average ∼55 CFU-APs/10 6 nucleated bone marrow cells [89]; in both sexes there is a decline in frequency with age. The exact nature of osteogenic stem cells is unclear; Muschler et al [90] advocate the term 'connective tissue progenitors' (CTPs) to encompass a heterogeneous group of multipotential stem cells responsible for musculoskeletal renewal and repair.…”
Section: Musculoskeletal Stem Cellsmentioning
confidence: 99%
“…One theory to explain these differences is that exposure to elevated levels of proinflammatory cytokines and antiinflammatory drugs might alter the activity status of MSCs. Many studies also have described an age-dependent decrease in the number of progenitor cells isolated from human bone marrow in elderly patients [28][29][30]. Currently, however, the literature and clinical practice demonstrate that adequate numbers of MSCs with satisfactory potential for chondrogenic differentiation may be obtained from elderly patients.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Currently, however, the literature and clinical practice demonstrate that adequate numbers of MSCs with satisfactory potential for chondrogenic differentiation may be obtained from elderly patients. Therefore, it is suggested that interventions using MSCs to regenerate cartilage in elderly people with OA are feasible [28][29][30].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%